2014
DOI: 10.1212/wnl.0000000000000855
|View full text |Cite
|
Sign up to set email alerts
|

The rare TREM2 R47H variant exerts only a modest effect on Alzheimer disease risk

Abstract: Objectives: Recently, 2 independent studies reported that a rare missense variant, rs75932628 (R47H), in exon 2 of the gene encoding the "triggering receptor expressed on myeloid cells 2" (TREM2) significantly increases the risk of Alzheimer disease (AD) with an effect size comparable to that of the APOE e4 allele. Methods:In this study, we attempted to replicate the association between rs75932628 and AD risk by directly genotyping rs75932628 in 2 independent Caucasian family cohorts consisting of 927 families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 30 publications
3
18
2
Order By: Relevance
“…We analyzed variants present by whole-genome sequencing in the NIMH AD Genetics Initiative Study, and used data on these variants in the AD Sequencing Project whole exome sequencing (ADSP) for replication ( Table 1 ). Family-based association analysis (FBAT) in the NIMH AD families yielded a p-value of 0.004 for R47H, consistent with our previous report in the same NIMH families (11) and confirmed in ADSP (p<3.45e-12; OR=4.5). Other rare variants in TREM2 were not present in more than ten statistically informative families, thereby preventing the computation of reliable p-values.…”
Section: Resultssupporting
confidence: 89%
“…We analyzed variants present by whole-genome sequencing in the NIMH AD Genetics Initiative Study, and used data on these variants in the AD Sequencing Project whole exome sequencing (ADSP) for replication ( Table 1 ). Family-based association analysis (FBAT) in the NIMH AD families yielded a p-value of 0.004 for R47H, consistent with our previous report in the same NIMH families (11) and confirmed in ADSP (p<3.45e-12; OR=4.5). Other rare variants in TREM2 were not present in more than ten statistically informative families, thereby preventing the computation of reliable p-values.…”
Section: Resultssupporting
confidence: 89%
“…Our analyses provide strong statistical evidence that the rare nonsynonymous variant rs75932628 in TREM2 substantially increases the risk for AD by approximately 2.7-fold. This OR is larger than that estimated in earlier analyses from our group (OR ~1.7) [33,38], which were based on only a small subset of the study samples available. In the first study ~3400 AD cases and controls were analyzed [33], whereas a total of ~5300 subjects were included in the extended and subsequently published analyses [38].…”
Section: Discussioncontrasting
confidence: 76%
“…Of note, the MAF of R47H seems to be even lower in the northern Han Chinese population (Yu et al, 2014) compared to European populations, and was not associated with LOAD risk in a Japanese population (Miyashita et al, 2014), suggesting this variant’s effect may be limited to European populations. More recently, a meta-analysis of family-based and case-control data supported the association of the R47H variant with increased LOAD risk, however the effect was much smaller (OR=1.67, 95% CI= 0.95-2.92) than that seen in other studies, including our own (Hooli et al, 2014). Slattery et al (2014) also confirmed this association while reporting a smaller odds ratio (OR=2.19, 95% CI= 1.04-4.51), while Finelli et al (2015) observed an odds ratio even higher than ours (OR=7.87, 95% CI=1.75-35.34).…”
Section: Discussionsupporting
confidence: 50%